Chemostratigraphic Architecture of Sandstone Facies Exposed along Auchi-Ighara Road, Mid-Western Nigeria - IKHANE, Phillips Reuben; ATEWOLARA-ODULE, Odunayo Christy; OYEBOLU, Olalekan Olayiwola; FAKOLADE, Omotoso Richard (GeoScience Engineering, 2022)
In this work, inorganic whole-rock geochemistry was applied to characterize the exposed sandstone facies along the Auchi-Ighara road Anambra basin Midwestern, Nigeria for distinction and correlation of the depositional units on the basis of the stratigraphic variation of geochemical trait. Fourteen representative samples collected from the outcrop were analyzed using Inductively Coupled Plasma-Mass Spectrometer (ICP-MS). From our analyses, ten major elements oxides, sixteen trace elements, and thirteen rare earth elements were obtained. The concentration of major elements in the samples range from 0.13 % and 53.71 % with SiO2, TiO2, Al2O3 and Fe2O3 being predominant. Other oxides found in the samples include K2O, CaO, Na2O, MgO and P2O5 indicating a recycled orogenic source of the grits from which the sandstone is derived. Trace elements concentration ranges between 0.017 ppm and 122.25 ppm; marked by the dominance of Zircon (Zr) which further asseverates orogenic recycling. The rare earth elements range in concentration from 0.01ppm and 5.53 ppm; the modal occurrence of Praseodymium (Pr) in this category is apparently indicative of deposition in an oxidizing environment. The appreciably high SiO2/Al2O3 ratio averages 11.2 in the samples is symptomatic of several cycles of sedimentation. Variation pattern of Ga/Rb and Al2O3/(CaO+MgO+K2O+Na2O) ratios connote a cooler and drier climatic condition after the sandstone deposition, which expectedly resulted to a decrease in hydrolytic weathering. Changes in sediment provenance are predicated on Cr/Al2O3, Cr/Na2O and Nb/Al2O3 ratio which indicate grits derivation from a more quartzose sedimentary and felsic sources that resulted from fluctuating paleoclimate during deposition. From the geochemical data, the paleoclimate and provenance of the sandstone facies were modelled and used for subdivision and correlation into two geochemical packages and five geochemical units. Keywords: Chemostratigraphy; Paleoclimate; Provenance; Weathering; Whole rock geochemistry.